The Role of Local Action Groups in the Process of Multifunctional Development of a Peripheral Region. A Case Study of the Region of Lublin, Poland - Danuta Guzal-Dec; Magdalena Zwolińska-Ligaj (Wieś i Rolnictwo)
The aim of the study is to describe the role of Local Action Groups (LAGs) under the Leader Programme in fostering entrepreneurship and employment in Lubelskie voivodeship. The hypothesis underpinning the study suggested that LAGs operating in rural areas of the Lublin region contribute insufficiently to job creation and provision of entrepreneurial incentives and play insufficient role in enhancing multifunctionality of rural areas. The study was based on document analysis and diagnostic surveys, including an interview questionnaire addressed to representatives of the offices of all 22 LAGs from the studied region. The results revealed that few projects were aimed at the development of non-agricultural functions in rural areas, and demonstrated insufficient involvement of LAGs in the implementation of projects in the bioeconomy sector, which is the key smart specialization of the region. In conclusion the authors assess the overall role of LAGs in creating jobs as marginal and call for paying more attention to the postulates of diversification assumptions resulting from the strategic development documents drafted for the region, including the Regional Innovation Strategy.